2002
DOI: 10.1111/j.1749-6632.2002.tb04183.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐Mediated Immune Response in MDMA Users After Repeated Dose Administration

Abstract: Acute administration of 3,4‐methylenedioxymethamphetamine (MDMA, “ecstasy”) produces time‐dependent immune dysfunction in humans. Recreational use of MDMA generally includes repeated drug consumption, often in association with other drugs, such as alcohol and cannabis. In the laboratory setting, repeated MDMA administration to healthy MDMA consumers produced a time‐dependent immune dysfunction similar to that observed with the ingestion of a single dose, and the first of the two administrations paralleled the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
6

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 33 publications
(83 reference statements)
0
53
0
6
Order By: Relevance
“…A decrease in plasma urea and lymphocytes were seen with an increase in neutrophils. It is of interest that a number of studies have indicated that MDMA may have an influence in suppressing immune function in humans due to depression of lymphocyte cell subsets such as T-helper cells and CD4 T-helper cells (Pacifici et al, 1999(Pacifici et al, , 2002. The biological significance of the deceased urea is unclear and is contrary to what would be predicted from case studies demonstrating rhabdomyolysis and renal failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A decrease in plasma urea and lymphocytes were seen with an increase in neutrophils. It is of interest that a number of studies have indicated that MDMA may have an influence in suppressing immune function in humans due to depression of lymphocyte cell subsets such as T-helper cells and CD4 T-helper cells (Pacifici et al, 1999(Pacifici et al, , 2002. The biological significance of the deceased urea is unclear and is contrary to what would be predicted from case studies demonstrating rhabdomyolysis and renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, there are no data available regarding plasma levels of MDMA in recreational 'ecstasy' consumers who do not develop medical complications (or are not apprehended by authorities). There have been several studies in which MDMA was administered to humans in a controlled laboratory setting and in which plasma pharmacokinetics of MDMA were measured (Helmlin et al, 1996;de la Torre et al, 2000de la Torre et al, , 2004Pacifici et al, 2001Pacifici et al, , 2002. However, these studies necessarily involved a limited dose range that was well below that reported by some MDMA users (Parrott, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Anecdotally, it appears that alcohol is taken in association with stimulants to get a stronger/better 'high'. Similarly, other stimulants such as MDMA/ecstasy, whilst in the presence of alcohol, show more significant physiopathological effects (Pacifici et al, 2002;Schifano et al, 2003a). In 15 cases mephedrone was ingested with stimulants.…”
Section: Mephedrone Use With Other Substancesmentioning
confidence: 99%
“…MDMA-mediated depression of the innate and adaptative immunity has been demonstrated in humans (Pacifici et al , 2002 as well as laboratory animals (Connor et al 2000(Connor et al , 2005. Despite the in vivo evidence, several in vitro studies have only presented a modest influence or even failed to show a significant MDMA-mediated immunosuppression (House et al 1995;Connor et al 2000;Camarasa et al 2010).…”
Section: Mdma In Immunosupression and Susceptibility To Toxicitymentioning
confidence: 99%
“…Although this observed immunosuppression is in agreement with the results from in vivo studies, it appears to contradict the increased MDMA-induced cytotoxicity we observed in our HepG2/PBMC co-culture. In relation to these immunosuppressive effects, it has been suggested that MDMA could probably be the cause of a greater susceptibility to infectious diseases through a reduction of pro-inflammatory events (Pacifici et al 2002;Boyle and Connor 2010;Carvalho et al 2010). …”
Section: Mdma In Immunosupression and Susceptibility To Toxicitymentioning
confidence: 99%